Pengaruh Minat Dan Motivasi Belajar Terhadap Prestasi Belajar Pendidikan Kewarganegaraan - Supardi Mahgi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
This study aims to analyze and test the truth of the hypothesis about the influence of Student Interest and Motivation on the Achievement of Citizenship Education Learning. Hypotheses tested include the influence of interest, motivation and student achievement in SMA Negeri in East Jakarta. The research used survey method on students of grade XI SMA N 48, SMA N 98, and SMA N 99 in East Jakarta with sample number of 108 people selected based on purposive sampling technique. Data analysis technique used is Regression Analysis Model with the help of SPSS 20 program to know the influence of independent variable with dependent variable. The statistical test uses the t-test. Data analysis using multiple correlation and regression techniques. The result of hypothesis testing shows that there is a significant influence of interest and motivation of learning together to the achievement of Civic Education of Senior High School students in East Jakarta, as evidenced by the value of Sig. = 0,000 <0,05 and Fcount = 28,538. The influence of interest on learning achievement is evidenced by the value of Sig. 0,000 <0,05 and thitung = 4,095. While the influence of learning motivation on learning achievement of Civic Education is evidenced by the value of Sig. 0,000 <0,05 and thitung = 5,088. Interest and motivation variables contributed 35.2% to the achievement of learning Civics, while 64.8% determined other variables that are not examined. Keywords: Interest, Learning Motivation, Learning Achievement Citizenship Education